A niche for cyanobacteria producing chlorophyll f within a microbial mat - Ohkubo, Satoshi (ISME J, 2017)
Acquisition of additional photosynthetic pigments enables photosynthetic organisms to survive in particular niches. To reveal the ecological significance of chlorophyll (Chl) f, we investigated the distribution of Chl and cyanobacteria within two microbial mats. In a 7-mm-thick microbial mat beneath the running water of the Nakabusa hot spring, Japan, Chl f was only distributed 4.0–6.5 mm below the surface, where the intensity of far-red light (FR) was higher than that of photosynthetically active radiation (PAR). In the same mat, two ecotypes of Synechococcus and two ecotypes of Chl f-producing Leptolyngbya were detected in the upper and deeper layers, respectively. Only the Leptolyngbya strains could grow when FR was the sole light source. These results suggest that the deeper layer of the microbial mat was a habitat for Chl f-producing cyanobacteria, and Chl f enabled them to survive in a habitat with little PAR.